Pengembangan Media Pembelajaran Video Animasi dengan Menggunakan Aplikasi Animaker Tentang Topik Tema "Fit Und Gesund" untuk Matakuliah Hören A1 - Rizky Abrar Damanik (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
The purpose of this study was to analyze the process and results of creating animated video learning media using the Animaker application with the theme "Fit und Gesund" for the Hören A1 subject. This development uses "Animaker" as a learning media for the A1 Listening subject, which adopts Plomp's theory as a development model. The results of this study are learning media for German in the form of a video "Fit und Gesund" using the Animaker application to support the A1 Listening subject. This media was developed based on the Netzwerk A1 book. Material experts gave a score of 95.8 for the learning media based on the Animaker application, which is included in the "Very Good" category. Media experts gave a score of 92.8 for this media. Based on the assessment criteria, this media is also categorized as "Very Good". Therefore, this Animaker application-based learning media is considered a feasible, practical, and effective media for Hören A1 skills.